Studying for the Enhancement Captured Images at Different LightnessDirections and Levels Distribution Based on Using Histogram EqualizationMethod - Al-Saleh, Anwar; Zuheri, Salema; Al-Zuky, Ali (Iraqi Journal of Science, 2024)
In this research we study the effect of the light distribution on the quality ofcaptured images under different amount of lightness conditions then enhancing thecaptured images by the imaging system using an adaptive histogram equalizationmethod and Lee method depending on the space YIQ depending on lightnesscomponent where use the reverse of this space to the basic RGB color space, thencorrected using the mathematical model based on human vision system. The resultswere analyzed and compute the quality of the enhancement images by using variousstatistical criteria based on the mean and standard deviation. Adaptive histogramequalization technique gives a high quality for the enhanced images for differentlightness conditions.